Callosal Agenesis and Interhemispheric Cysts - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Imaging studies of 25 cases of agenesis of the corpus callosum with interhemispheric cyst were retrospectively reviewed at the University of California, San Francisco, and Harvard Medical School, Boston.